Tendons - Sözen, Hasan (IntechOpen, 2019)
Mankind has reached its present physical form through evolution of the movement system. Muscles, bones, and joints are the most important components of the movement system. Muscles are active elements, while bones and joints are passive elements. But to bring about movement, these three elements must work together. Tendons are round, oval, or flat tissues that connect muscles to bones. Muscle, tendon, or ligament injuries prevent motion so this is an important issue in trauma. If muscle, tendon, or ligament injuries occur together with vessel or nerve injury, it may be life threatening. The cause of injury might differ from a simple sports injury to a serious traffic accident. Muscles, bones, and joints have taken their place in the literature, but it would be wrong to say the same for tendons. This book describes tendons from different perspectives, thus providing the missing information in the literature. I hope that this book will be useful for anyone who wants to read about new perspectives on tendons. I also hope that it will inspire researchers working in this field.